THE ECONOMICAL FEASIBILITY OF SOYBEAN FARMING WITH THE INTEGRATED CROP MANAGEMENT (ICM): CASE STUDY AT NIMBOKRANG DISTRICT JAYAPURA - Pandu Laksono; Adnan Adnan (Widyariset, 2011)
The objective of this research was to determine the economical feasibility of soybean farming with the Integrated Crop Management (ICM) approach. This research was conducted in April–December 2009 and took place in Nimbokrang District, Jayapura Regency, Papua Province. Integrated Crop Management components were the use of high yield seeds (Ijen, Burangrang, Tanggamus, Seulawah), perfect soil tillage, balanced fertilizer and spacing. The research involved two cooperative farmers which apply ICM method and one non-cooperator farmer who apply the farmers system, using Ijen variety that are already common planted by local farmers. The results showed that the variety of Ijen with ICM method obtained the highest yields 2.15 tonn/ha with B/C ratio was 1.47,whereas Burangrang yields was 1.89 tonn/ha with B/C ratio 1.24, Tanggamus yields was 1.68 tonn/ha with B/C ratio 1.04 and Seulawah yield was 1.28 tonn/ha with B/C ratio 0.64. All of the varieties cultivated by the ICM method were feasible except Seulawah. Soybean farming using Ijen, Burangrang and Tanggamus varieties were feasible to develop with MBCR value of Ijen is 2.47, Burangrang 2.24, and Tanggamus 2.04.